Social accountability: A national framework for Turkish medical schools. (1st February 2021) - Sayek, Iskender; Turan, Sevgi; Batı, A. Hilal; Demirören, Meral; Baykan, Zeynep
Abstract: Purpose: To define recommendations to the medical schools in Turkey about social accountability which meets the local needs. Methodology of the study: The Association of Evaluation and Accreditation of Medical Education Programs (TEPDAD-Turkey) Social Accountability working group planned a study to determine national recommendations for social accountability of medical schools in two-stages. Delphi technique was used to develop the recommendations and finalize the recommendations in the first stage in which 61 members from 30 different institutions participated. Qualitative analysis was used for open questions in the first round and quantitative analysis for the data which is collected with a rating scale in the second and third rounds of the Delphi study. In the second stage, the recommendations were reviewed and finalized in a consensus workshop in which 68 members from 39 different institutions participated. Results: In the Delphi study 63 recommendations were classified under five themes: the health needs of the society, health service delivery, institutional structure and management, educational program and implementation and development and evaluation of social accountability. In the consensus workshop, the 63 recommendations were evaluated and of which 54 of 63 recommendations were agreed upon. Conclusion: A national framework has been developed by including a wide range of experts from different institutions for the social accountability of medical schools in Turkey. Developing recommendations in a local context will enhance the conceptualization of the recommendations of social accountability in the medical schools. As an accreditation body embedding the principles in the national standards will have a further impact on this process.